Our Daily Bread : What is the Evidence on Comparing Cash versus Food Transfers? - Gentilini, Ugo (World Bank Group, Washington, DC, 2014)
This paper reviews key issues in the 'cash versus food' debate, including as they relate to political economy, theory, evidence, and practice. In doing so, it benefited from a new generation of 12 impact evaluations deliberately comparing alternative transfer modalities. Findings show that differences in effectiveness vary by indicator, although they tend to be moderate on average. In some cases differences are more marked (i.e., food consumption and calorie availability), but in most instances they are not statistically significant. In general, transfers' performance and their difference seem a function of the organic and fluid interactions among factors like the profile and 'initial conditions' of beneficiaries, the capacity of local markets, and program objectives and design. Costs associated with cash transfers and vouchers tend to be substantially lower relative to food. Yet methods for cost-effectiveness analysis vary and need to be more standardized and nuanced. The reviewed evaluations are helping to shift the debate from one shaped by ideology, political economy and 'inference' of evidence to one centering on robust and context-specific results.